Representations of desert Arabs as colonial subjects in the contemporary French novel: a study of desert by Le Clezio (2015)
Stereotypes of the Islamic world, which were generated by colonial French writers and denounced by their North African counterparts, usually degraded the Orient and justified colonialism. This article focused on the representations of the colonised Maghrebian Arabs in the novel of Le Clezio, a contemporary French writer. The study applied the postcolonial literary theory to explore the experiences of race, representation and difference in relation to the colonial discourse of Orientalism and Fanon's dichotomy between the coloniser and the colonised with a view to establishing the colonial assumptions permeating the novel titled Desert. The nomadic Arabs were dehumanised, debased, gerontified and infantilised while their virtues were negated and trivialised by Europeans, who, conversely influenced by Occidentalist self-affirmation, portrayed themselves as superior and powerful people whose intervention was to take out an eccentric, criminal and outlawed Islamic leader. Flis descendants in the colonised 'City' were classified as oppressors of women, moribund and wretched people who saw Europe as the Eldorado. These various representations of the Tuaregs as the demonic 'Other' of the European 'Self underpinned the writer's intention to expose the influence of colonial mentality, a result of hegemonic western discourse, on Iris fellow Europeans.